Urinary incontinence among women in sub-Saharan Africa – an overview - Omeke, Chidimma A.; Azuka, Charles E. (Frontiers in Urology, 2023)
Urinary Incontinence, the uncontrolled or involuntary loss of urine, is a prevalent condition among women that is frequently underdiagnosed and underreported, particularly in sub-Saharan Africa (SSA). The social stigma attached to urinary incontinence contributes to low presentation rates for care, and the help-seeking behaviour of SSA women with urinary incontinence in this region. Thus, the occurrence of urinary incontinence imposes a considerable burden on women in SSA, leading to physical, social, and psychological complications. A multitude of challenges, such as limited availability of urogynecological, facilities corruption, etc, have collectively contributed to the scarcity of information on how to manage urinary incontinence in this region. The commonplace management of urinary incontinence is the use of adult diapers, mostly among older women in this region. While it is essential to carry out more research to comprehend the impact of urinary incontinence on women in Sub-Saharan Africa and to promote awareness of medical and surgical interventions; It is recommended that the governing bodies of these regions enhance their endeavours to provide essential facilities and training a skilled workforce to manage this condition at a subsidized cost.